REDESIGN WEBSITE BUKU TAMU KOTA DENPASAR DI DINAS KOMUNIKASI, INFORMATIKA DAN STATISTIK KOTA DENPASAR - Putu Chandra Mayoni; I Gede Santi Astawa; Ida Ayu Gde Suwiprabayanti Putra (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
The Denpasar City Guestbook is a digital platform for managing and recording visitor data in government agencies to improve service effectiveness. This study aims to redesign the website interface by implementing User Interface (UI) and User Experience (UX) principles. The methods employed include user requirements analysis, prototype design, and website development implementation using HTML, CSS. The results show significant improvements in website quality through menu structure simplification, color scheme consistency, typography, layout, and the addition of visual elements including submit buttons. This redesign has successfully created a more responsive and efficient interface, making it easier for the public to record visits and provide feedback to the government for enhancing agency services